The Effect of Internet Use on Improving Student Learning Outcomes - Prasetyo, Mohammad Mulyadi; Nurhidayah, Nurhidayah (Journal of Education Technology, 2021)
Students have difficulty in learning, so that it has an impact on low learning outcomes. The low student learning outcomes can be caused by the quality of learning, one of which is the lack of learning reference sources. The purpose of this study was analyze improvement of students' Biology learning outcomes before and after the application of internet use. This type of research is a quasi-experimental design through the Nonequivalent Control Group Design. The subjects in this study were students of class IX, which in this study used two classes, namely the control class and the experimental class. Learning in the control class is the usual lecture method, while in the experimental class it is done by applying the method of using the internet. The acquisition of learning outcomes data using the learning outcomes test (pretest-posttest). The hypothesis test using covariance analysis aims to determine whether there is an effect of the independent variable on the dependent variable. The results of the data obtained indicate that the effect of using the internet can improve student learning outcomes. The results of inferential statistical analysis obtained the value of Sig.count 0.000 with = 0.05. The results of the analysis indicate that the value of Sig.count is greater than (0.000 > 0.05) so Ho is rejected and H1 is accepted. So it can be concluded that in the learning process by utilizing the internet as a complement to conventional learning can improve student learning outcomes. Thus the internet as a learning resource can improve learning outcomes.